The Sloping Land Conversion Program in China: Effect on Rural Households' Livelihood Diversification - Zhen Liu (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
By overcoming the barriers that limit access to financial liquidity and human resource, the Sloping Land Conversion Program (SLCP) can promote rural livelihood diversification. This paper examines this effect using a household survey data set spanning the 1999 implementation of the Sloping land conversion program. Our results show that SLCP works as a valid external policy intervention on rural livelihood diversification. In addition, the findings demonstrate that there exist heterogeneous effects of SLCP implementation on livelihood diversification across different rural income groups. The lower income group was more affected by the program in terms of income diversification.
Keywords: Q12; Q15; Q58; 330; Sloping Land Conversion Program; China; Livelihood diversification; Income diversity index; Identification condition; Difference in differences